Collagen mimetic peptide repair of the corneal nerve bed in a mouse model of dry eye disease - Wareham, Lauren K.; Holden, Joseph M.; Bossardet, Olivia L.; Baratta, Robert O.; Del Buono, Brian J.; Schlumpf, Eric; Calkins, David J. (Frontiers in Neuroscience, 2023)
The intraepithelial sub-basal nerve plexus of the cornea is characterized by a central swirl of nerve processes that terminate between the apical cells of the epithelium. This plexus is a critical component of maintaining homeostatic function of the ocular surface. The cornea contains a high concentration of collagen, which is susceptible to damage in conditions such as neuropathic pain, neurotrophic keratitis, and dry eye disease. Here we tested whether topical application of a collagen mimetic peptide (CMP) is efficacious in repairing the corneal sub-basal nerve plexus in a mouse model of ocular surface desiccation. We induced corneal tear film reduction, epithelial damage, and nerve bed degradation through a combination of environmental and pharmaceutical (atropine) desiccation. Mice were subjected to desiccating air flow and bilateral topical application of 1% atropine solution (4x daily) for two weeks. During the latter half of this exposure, mice received topical vehicle (PBS) or CMP (200 µm (Pro-Pro-Gly)7, 10 µl) once daily, two hours prior to the first atropine treatment for that day. After euthanasia, cornea were labeled with antibodies against βIII tubulin to visualize and quantify changes to the nerve bed. For mice receiving vehicle only, the two-week desiccation regimen reduced neuronal coverage of the central sub-basal plexus and epithelial terminals compared to naïve, with some corneas demonstrating complete degeneration of nerve beds. Accordingly, both sub-basal and epithelial βIII tubulin-labeled processes demonstrated increased fragmentation, indicative of nerve disassembly. Treatment with CMP significantly reduced nerve fragmentation, expanded both sub-basal and epithelial neuronal coverage compared to vehicle controls, and improved corneal epithelium integrity, tear film production, and corneal sensitivity. Together, these results indicate that topical CMP significantly counters neurodegeneration characteristic of corneal surface desiccation. Repairing underlying collagen in conditions that damage the ocular surface could represent a novel therapeutic avenue in treating a broad spectrum of diseases or injury.